A new association between CDK5RAP2 microcephaly and congenital cataracts. (22nd December 2017) - Alfares, Ahmed; Alhufayti, Ibtihal; Alsubaie, Lamia; Alowain, Mohammed; Almass, Rawan; Alfadhel, Majid; Kaya, Namik; Eyaid, Wafaa
Abstract: Introduction: Primary microcephaly type 3 is a genetically heterogeneous condition caused by a homozygous or compound heterozygous mutation in CDK5 regulatory subunit associated protein 2 (CDK5RAP2) and characterized by reduced head circumference (<5th percentile) with additional phenotypes varying from pigmentary abnormalities to sensorineural hearing loss. Until now, congenital cataracts have not been reported in patients with primary microcephaly type 3. Clinical report: We report multiple affected family members from a consanguineous Saudi family with microcephaly and congenital cataracts. We utilized a next‐generation sequencing–based microcephaly gene panel that revealed a CDK5RAP2 variant (c.4055A>G; p.Glu1352Gly) as the most plausible candidate for the likely etiology in this family. Then we performed family segregation analysis using Sanger sequencing, autozygosity mapping, and whole exome sequencing, all of which revealed no other possible disease‐causing variants. Conclusion: Here we report on a new clinical manifestation of CDK5RAP2 and expand the phenotype of primary microcephaly type 3.